The Short- and Long-Run Determinants of Less- Educated Immigrant Flows into U.S. States - Nicole B. Simpson; Chad Sparber (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2012)
We use a gravity model of migration and alternative estimation strategies to analyse how income differentials affect the flow of immigrants into U.S. states using annual data from the American Community Survey. We add to existing literature by decomposing income differentials into short- and long-term components and by focusing on newly arrived less-educated immigrants between 2000-2009. Our sample is unique in that the vast majority of our observations take zero values. Models that include observations with zero flow values find that recent male immigrants respond to differences in (short-term) GDP fluctuations between origin countries and U.S. states, and perhaps to (long-term) trend GDP differences as well. More specifically, GDP fluctuations pull less-educated male immigrants into certain U.S. states, whereas GDP trends push less-educated male immigrants out of their countries of origin. Effects for less-educated women are less robust, as GDP coefficients tend to be much smaller than for men.
Keywords: J61; E01; 330; Immigration; Macroeconomics; GDP; Gravity